If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -22 = -26 + 2n Reorder the terms: -22 + 6n = -26 + 2n Solving -22 + 6n = -26 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. -22 + 6n + -2n = -26 + 2n + -2n Combine like terms: 6n + -2n = 4n -22 + 4n = -26 + 2n + -2n Combine like terms: 2n + -2n = 0 -22 + 4n = -26 + 0 -22 + 4n = -26 Add '22' to each side of the equation. -22 + 22 + 4n = -26 + 22 Combine like terms: -22 + 22 = 0 0 + 4n = -26 + 22 4n = -26 + 22 Combine like terms: -26 + 22 = -4 4n = -4 Divide each side by '4'. n = -1 Simplifying n = -1
| 10y^3=7y+1 | | 3-8x-5x+3= | | 7x-4=4(x+3) | | -16+2y+20-5y=-7-4 | | 2160=27000(0.04)T | | Y-12=-7.33 | | 15x+3+x= | | -4*16*-25= | | 15x+30=32x | | 2.5(n)=36 | | w-13w=0 | | -5=4n+7 | | 3.5(n)=36 | | 33=-6(4d+9) | | 10x+15=150 | | 3x-3=14x+8 | | 0.25(8x+6)-x=29.5 | | 8.5(n)=36 | | 0.25(8x+6)-x=19 | | 12+13+5+n=9*8 | | 10y*3=7y+1 | | 37.7=2(3.14)r | | Y-12=7.33 | | (k-5)(k-4)=0 | | 4p-3=6p+5 | | 136=.5h(10+7) | | 46=2(2x+5)+2x | | X-5=2y | | -2t-7+3t-2=2 | | x-5+74=180 | | -6+x/4=-8 | | 7h=84 |